Behavioral Responses of Timor Deer (Rusa timorensis) Fawns to the Presence of Visitors at the Semarang Zoo - Kasiyati, Kasiyati; Resa, Ris Setya; Prihatiningsih, Liliana Puri; Aminullah , Aditya Alrais; Setiawan, Hendrik Tri (Faculty of Veterinary Medicine, Udayana University and Published in collaboration with the Indonesia Veterinarian Association, 2026)
Animal behavior is a directed activity resulting from environmental stimuli involving the coordination of the nervous, endocrine and muscular systems. The presence of visitors at the zoo, whether on weekdays or weekends, can significantly impact animal behavior. Deer avoid contact with humans, but conditions at the zoo, which differ from the wild, require deer to be able to interact with humans. The purpose of this study was to evaluate the behavioral responses of Timor deer (Rusa timorensis) fawns to the presence of visitors on weekdays and weekends in the ex-situ conservation area of Semarang Zoo of Central Java, Indonesia. The behavioral responses observed included aggressive, locomotor, eliminative, self-grooming, resting, feeding and social behaviors. This study was conducted over 21 days by observing the behavior of nine Timor deer fawns, consisting of six females and three males, that were still suckling their does. The observation method used was scan-sampling, which was conducted in the morning, noon and afternoon, with a two-hour observation interval. The data obtained were analyzed using a t-test. The presence of visitors on weekdays and weekends had no effect (p>0.05) on all observed behavioral parameters of Timor deer fawns. However, the percentage of locomotion, eating, self-care, social and elimination behaviors was higher in the morning with a longer duration, while the percentage of rest was longer in the afternoon. This study concluded that the behavioral responses of Timor deer fawns at the ex-situ conservation area to visitors were consistent on both weekdays and weekends. The Timor deer were accustomed to the presence of visitors, allowing them to exhibit their natural behavior still.